MENILAI AKSESIBILITAS AIR MINUM (STUDI KASUS: AKSESIBILITAS AIR BERSIH BAGI MASYARAKAT MISKIN DI KOTA SEMARANG) - Maryono, Maryono (Universitas Diponegoro, 2007)
Water accesibility for the poor people is one of the indicator on water supply and delivary sistem in the cities. Batram and Howard have make a catagorization for the accessibility. There are three level; law accessibility, medium accessibility and hight accessibility. The Accessibility in Semarang City for is at the medium. But the people must spent 5 % from the revenue every month to acces the water. This situation is bad, regarding of the standart, the should spent not more then 3 %.